CREATIVITY OF STUDENT AS UNIVERSAL COGNITIVE CREATIVE ABILITY - Vera A. Kurina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article the features of organization of cognitive activity are presented on the basis of креативного approach in institution of higher learning of culture. The special value in the creative educating and education is acquired by modern pedagogical technologies, methodologies, forms, methods and facilities.